Clinical Decision Making in Dysmorphology- Emerging Role of Artificial Intelligence - Mahwish, Nayesha; Saherawala, Batul Abdeali; Jhancy, Malay (British Journal of Healthcare and Medical Research, 2022)
The human genome codes for more than 22,000 genes, many of which have been implicated in human diseases. These genetic diseases are often associated with dysmorphic facial features. Dysmorphic features occur due to premature closure of cranial sutures resulting in changes in skull shape and facial characteristics. Assessment of dysmorphic features is a crucial component of genetic consultations. This requires a great deal of clinical experience and expertise and tends to be subjective. Artificial intelligence-based analysis can come in handy for quick and accurate identification of dysmorphic features. This review explores the role played by artificial intelligence in identifying dysmorphic facies and diagnosing various genetic diseases in children.